(Breaking) Intergenerational Transmission of Mental Health - Aline Bütikofer; Rita Ginja; Krzysztof Karbownik; Fanny Landaud (Center for Economic Studies and ifo Institute (CESifo), 2023)
We estimate health associations across generations and dynasties using information on healthcare visits from administrative data for the entire Norwegian population. A parental mental health diagnosis is associated with a 9.3 percentage point (40%) higher probability of a mental health diagnosis of their adolescent child. Intensive margin physical and mental health associations are similar, and dynastic estimates account for about 40% of the intergenerational persistence. We also show that a policy targeting additional health resources for the young children of adults diagnosed with mental health conditions reduced the parent-child mental health association by about 40%.
Keywords: I14; I18; J12; J62; 330; mental health; intergenerational persistence; dynastic effects; public policy